2012
DOI: 10.1080/15533174.2012.680151
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Crystal Structures, and Urease Inhibitory Properties of Two Isostructural Dinuclear Zinc(II) Complexes With Schiff Base 5-Methoxy-2-[(2-methylaminoethylimino)methyl]phenol

Abstract: Two new isostructural dinuclear zinc(II) complexes with Schiff base 5-methoxy-2-[(2-methylaminoethylimino)methyl]phenol were prepared and characterized by elemental analyses, infrared spectroscopy, and single-crystal X-ray diffraction. Both complexes are phenolate O-bridged dinuclear zinc(II) compounds with crystallographic twofold rotation axis symmetry. The Schiff base acts as a tridentate chelating ligand. The Zn atom is five-coordinated in a square pyramidal geometry. The preliminary urease inhibitory acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…It is also important to highlight the zinc complexes obtained by You and co-workers (2009) ( 52 and 53 ) and Wang and co-workers (2012) ( 54 and 55 ); however, these complexes presented only moderate anti-urease activities (70 µM < IC 50 < 100 µM) ( Fig. 9 ) [57] , [58] .
Fig.
…”
Section: Schiff Base Metal Complexes As Urease Inhibitorsmentioning
confidence: 87%
See 2 more Smart Citations
“…It is also important to highlight the zinc complexes obtained by You and co-workers (2009) ( 52 and 53 ) and Wang and co-workers (2012) ( 54 and 55 ); however, these complexes presented only moderate anti-urease activities (70 µM < IC 50 < 100 µM) ( Fig. 9 ) [57] , [58] .
Fig.
…”
Section: Schiff Base Metal Complexes As Urease Inhibitorsmentioning
confidence: 87%
“…Because of the diversity of its biological functions and its low toxicity [47] , zinc has been a starting point for the design of urease inhibitors based on Zn-complexes. Notably, Zn 2+ by itself has no anti-urease activity [44] , [52] , [53] , [54] , [55] , [56] , [57] ; however, when it is used in the form of a zinc-complex, this metal enhances the inhibitory activity of the ligand.…”
Section: Schiff Base Metal Complexes As Urease Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two novel isostructural dinuclear zinc(II) complexes ( 26 and 27 ) based on Schiff base were synthesised 56 . It was found that the Schiff base was a tridentate chelating and the Zn atom in complexes was five-coordinated in a square pyramidal geometry.…”
Section: Metal-based Urease Inhibitorsmentioning
confidence: 99%